A Mixed‐Metal Oxides/Graphitic Carbon Nitride: High Visible Light Photocatalytic Activity for Efficient Mineralization of Rhodamine B. Issue 12 (19th May 2017) - Huy, Bui The; Thao, Chu Thi Bich; Dao, Van‐Duong; Phuong, Nguyen Thi Kim; Lee, Yong‐Ill
Abstract : Novel photocatalysts in the form of zinc oxide‐zinc bismuth oxide (mixed‐metal oxide [MMO]) and graphitic carbon nitride (CN) hybrid composites are developed via a co‐precipitation method followed by calcination at 520 °C. The as‐prepared MMO‐CN hybrid composites are evaluated on the basis of their photocatalytic activities for Rhodamine B (RhB) in aqueous solutions under visible light irradiation. The strong electronic coupling between two components within the MMO‐CN heterostructure, which suppresses the photogenerated recombination of electrons and holes to a remarkable extent, is revealed. The prepared composites exhibit an excellent photocatalytic activity, leading to more than 95% of RhB degradation at an initial concentration of 50 mg L −1 using 0.5 g catalyst per liter in 90 min, along with 25 min of the RhB half‐life time. The excellent photocatalytic mineralization of MMO‐4.0CN by visible light irradiation can be attributed to the synergic effects for high and charge transfer between MMO and CN as well as efficient separation of photogenerated electrons and holes. The species most responsible for photodegradation is holes ( h + ) with moderate and minor contributions by the superoxide anion and hydroxyl radicals, respectively. These results attest to a green, low cost, and high efficiency photocatalyst for environmental remediation. Abstract : Novel mixed‐metal oxides/graphitic carbon nitride composites that are coupled using co‐precipitation exhibit excellent photocatalytic activity to Rhodamine B. The mechanism for visible light photocatalytic mineralization of prepared sample is proposed. The prepared sample exhibits high chemical stability and efficiency as photocatalyst for environmental remediation.